STRATEGI RUMAH SAKIT DALAM MENGHADAPI KRISIS PUBLIC RELATIONS MENURUT PERSPEKTIF FIQH MUAMALAT - Hasan, Safari (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
The hospital is a complex organization and That Is Solid BECAUSE nature of capital, Solid Labor, Technology and ALSO Solid Solid problems. The hospital is a place of health promotion, prevention and cure of disease, improving health and Recovery Patients Performed multi-Discipline BY VARIOUS Posted professionally educated and trained group of Discipline concerning medical, legal, economic, social, and management. Consumer complaints against hospitals, CAN cause problems For hospitals The AS is known crisis public relations. A crisis can be defned as Extraordinary Events OR circuit events affecting the integrity of products, as well as the organization’s reputation Financial Stability, OR From the worker’s health, community, public OR IN area. Step Management of Crisis PR include (1) MAKE draft development strategy Management of Crisis PR (aktiitas Preparation, directing conduct, a statement holding prepare, prepare PT response, development of strategies to prepare Intermediaries Media.), (2) Implementation Phase (do Communication storey, alternative location determining, updating statement holds). Public Relations Management Activity husband studied CAN BE Fiqh Muamalat through Law Shulhu OR mediation.Keywords: hospital, PR crisis management, fqh muamalah, Shulhu